2023
DOI: 10.1111/iej.13948
|View full text |Cite
|
Sign up to set email alerts
|

The bioceramic sealer iRoot SP promotes osteogenic differentiation of human stem cells from apical papilla via miR‐141‐3p/SPAG9/MAPK signalling pathway

Abstract: AimThe premixed bioceramic sealer iRoot SP that is widely used clinically has been reported to kill bacterial biofilms and promote osteogenic differentiation of human stem cells from the apical papilla (hSCAPs). Although miR‐141‐3p has been substantiated to be involved in the osteogenic process, the underlying mechanisms remain unclear. The aim of this study was to investigate the role of miR‐141‐3p in osteogenic differentiation and underlying mechanisms of iRoot SP‐treated hSCAPs.MethodologyhSCAPs were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A comparison of AH Plus and zinc-oxide eugenol sealers did not indicate any osteogenic potential (Giacomino et al, 2019). A recent study analysed the osteogenic response of IRoot SP extracts on human stem cells from periapical papilla previously conditioned with osteogenic conditioned medium (Xue et al, 2023); their results revealed the osteogenic differentiation of human stem cells by inhibiting the miR-141-3p pathway.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A comparison of AH Plus and zinc-oxide eugenol sealers did not indicate any osteogenic potential (Giacomino et al, 2019). A recent study analysed the osteogenic response of IRoot SP extracts on human stem cells from periapical papilla previously conditioned with osteogenic conditioned medium (Xue et al, 2023); their results revealed the osteogenic differentiation of human stem cells by inhibiting the miR-141-3p pathway.…”
Section: Discussionmentioning
confidence: 97%
“…Previous histological and immunohistochemical studies have indicated the presence of a large number of multipotent cells and mesenchymal stem cells (MSCs) in the periapical area (Liao et al, 2011), such as human periapical cyst MSCs (Marrelli et al, 2013) and human stem cells from periapical papilla (Xue et al, 2023). This area is also characterized by a large vascularization network, similar to those of periodontal ligaments (Davey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding gene expression, previous reports have highlighted the ability of calcium silicate‐based sealers to induce the differentiation of periodontal ligament stem cells into osteoblasts and cementoblasts (Sanz et al, 2020; Xue et al, 2023). The sealers tested were able to induce overexpression of the CEMP‐1, ALP, and COL1A1 genes in the first days of exposure, particularly in the case of TFbc.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, 1 × 10 5 cells were resuspended in 100 mL of phosphate buffer saline (PBS) with 1% FBS and the following fluorescence-conjugated specific monoclonal antibodies: CD14, CD20, CD34, CD45, CD73, CD90, and CD105 (Miltenyi Biotec, Bergish Gladbach, Germany). The characterization process was performed using the methodology of previous similar studies [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The expression of osteo/cemento/odontogenic markers by hPDLSCs co-cultured with the materials was evaluated through real-time quantitative polymerase chain reaction (RT-qPCR). This assay acts as an indicator of cell differentiation and has also been used in previous similar studies [ 33 , 41 ]. AHP was excluded from the marker expression assay because of its negative results in the hPDLSC cytocompatibility assays.…”
Section: Methodsmentioning
confidence: 99%